2019
DOI: 10.1002/marc.201900019
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characterization of Biomaterials Directs Additive Manufacturing of Strontium‐Substituted Bioactive Glass/Polycaprolactone Microfibers

Abstract: Additive manufacturing via melt electrowriting (MEW) can create ordered microfiber scaffolds relevant for bone tissue engineering; however, there remain limitations in the adoption of new printing materials, especially in MEW of biomaterials. For example, while promising composite formulations of polycaprolactone with strontium‐substituted bioactive glass have been processed into large or disordered fibres, from what is known, biologically‐relevant concentrations (>10 wt%) have never been printed into ordered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…Using other approaches, such as FDM, [78] or a hybrid MEW-solvent printing approach, can be used to significantly increase the weight percent of additives, with the latter achieving a 33 wt% of strontium-substituted bioactive glass in PCL. [79] Approaches such as these which achieve a high core mineral content have many advantages for bone TE applications, and may be further enhanced by our developed nnHA coating. In summary, we have demonstrated that our nnHA coating procedure closely mimics the nanoarchitecture, composition, and crystal structure of native bone, and has great potential for coating various surfaces and structures to achieve a more bone-mimetic topography.…”
Section: Discussionmentioning
confidence: 99%
“…Using other approaches, such as FDM, [78] or a hybrid MEW-solvent printing approach, can be used to significantly increase the weight percent of additives, with the latter achieving a 33 wt% of strontium-substituted bioactive glass in PCL. [79] Approaches such as these which achieve a high core mineral content have many advantages for bone TE applications, and may be further enhanced by our developed nnHA coating. In summary, we have demonstrated that our nnHA coating procedure closely mimics the nanoarchitecture, composition, and crystal structure of native bone, and has great potential for coating various surfaces and structures to achieve a more bone-mimetic topography.…”
Section: Discussionmentioning
confidence: 99%
“…M w = 45.6 × 10 3 [ 67,68] M w = 50 kDa [64] [ 5,67,68,64,15] Capa 6500C High clarity grade when molten M w = 50 × 10 3 a) [69] MFI = 7 b) [ 69,70] Capa 6506 Medical grade M w = 50 kDa [29] [29]…”
Section: Why Pcl?mentioning
confidence: 99%
“…Published by Elsevier B.V. L) Reproduced with permission. [64] Copyright 2019, Wiley-VCH GmbH. M) Reproduced with permission.…”
Section: Dissolvable Channelsmentioning
confidence: 99%
“…The perfect material needs to comply with the following parameters: (a) the adequate mechanical properties to allow deposition, (b) the ability to hold its 3D structure after deposition, (c) a supportive, cell‐friendly milieu at all stages of the bioprinting process. One major drawback is the focus of current research to adapt traditional materials to bioprinting processes and hardware, instead of using bioprinting parameters as blueprints from which new materials are developed (Paxton et al, ). Depending on the type or printing modality, specific concerns (e.g., shear stress, temperature, and chemical reaction‐based cell damage), arise based on deposition methodology and the specific biomaterial used; as crosslinking, curing kinetics, and chemical properties of the material will directly influence the printing process (Skardal & Atala, ).…”
Section: Inkjet 3d Bioprintingmentioning
confidence: 99%